The Impact Of Assistance Program P4S (Pusat Pelatihan Pertanian Perdesaan Swadaya) To The State Of the Effort Aquaculture In Cages In Kampar Sub District Kampar Regency Of Riau Province - Elviana, Nella; Nugroho, Firman; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conduted on April 2015. The purpose of this research was to identity production and factor of production, fish farmer income and ekspenditure, and to identity the impact of assistance P4S program to the state of the effort aquaqultur in cages. This research was analyzes factors of production, increasing production, fish farmer income and ekspenditure after the implementation of P4S program. The method used in this research is the survey method. Sampling design in this research uses purposive sampling to determine research location and for the intake of sample in every sample villages using the area sampling, so that the research locations are obtained at 7 villages in one same sub district, i.e. sub district of Kampar, Kampar Regency Of Riau Province, and then taken 14 people sample to be used as respondents.The results of the research shows the that P4S program could cause total of production increased and factors production could be better than before, and as well can improve the income of fish farmer, it means that P4S program give a positive impact to the state of the effort. The research also shows the utilization of the time the fish farmer can be more productive and the effort of aquaqulture can be growth than before, so prosperty levels of life can be increased.Keywords : Assistance, Program P4S, production, Fish Farmer Income